2016
DOI: 10.1016/j.bmhimx.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriemia relacionada con catéter venoso central: incidencia y factores de riesgo en un hospital del occidente de México

Abstract: In addition to strategies of maximum caution when placing or manipulating the catheter, we recommend decreasing, as much as possible, disconnects between the CVC and infusion line. Antibiotics showed a protective effect, but the outcome is uncertain and promotion of antimicrobial resistance should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…Así, se observa el predominio S. aureus Meticilino resistente (SAMR) y de E. faecalis. Asimismo en un estudio de cohorte prospectivo en un hospital de concentración del occidente de México, los microorganismos identificados fueron cocos Gram positivos (37.5%, n = 6), bacilos Gram negativos (37.5%, n = 6) y Candida albicans (25%, n = 4) (Lona, López, Barragána, Pérez & Ascencio, 2016).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Así, se observa el predominio S. aureus Meticilino resistente (SAMR) y de E. faecalis. Asimismo en un estudio de cohorte prospectivo en un hospital de concentración del occidente de México, los microorganismos identificados fueron cocos Gram positivos (37.5%, n = 6), bacilos Gram negativos (37.5%, n = 6) y Candida albicans (25%, n = 4) (Lona, López, Barragána, Pérez & Ascencio, 2016).…”
Section: Discussionunclassified
“…Los índices de incidencia nacional de IAAS reportados en centros de referencia oscilan entre 8 -24/1000 días-paciente (Pérez, 2016). La prevalencia de IAAS en el Paraguay reportados en centros de referencia oscila entre 11 -30%.…”
Section: Introductionunclassified
“…A recent study suggested biofilms were responsible for 65% of nosocomial infections in this country [ 20 ]. As an example, in 2016, 204 patients with a CVC (Central Venous Catheter) between 4 and 6 years under critical condition were monitored after placing this device in the intensive care area for seven days, taking two blood cultures daily (one through this catheter and another through the peripheral vein) [ 21 ]. The cultures were analyzed using a MicroSan autoSCAN-4 System, revealing the presence of microorganisms in the blood cultures of 24 patients, of which nine were not related to the catheters and 15 were related to colonized catheters.…”
Section: Relevance Of Biofilms In the Biomedical Fieldmentioning
confidence: 99%
“…were found in the cultures. The researchers concluded that the contamination had an external origin and was not caused by commensal germs on the skin [ 21 ].…”
Section: Relevance Of Biofilms In the Biomedical Fieldmentioning
confidence: 99%
“…Un ejemplo de esto es la higiene de manos 11 , uso de apósito estéril transparente 12 , programas de educación establecidos en correcta instalación y mantenimiento de acceso vasculares [13][14] , uso de clorhexidina como antiséptico para la preparación de la piel [15][16][17] , uso de la barrera máxima durante la inserción y mantenimiento [18][19][20][21][22][23][24][25] , así como uso de listas de verificación (check-list) de procedimientos 26 .…”
Section: Introductionunclassified